Effects of Nigella sativa, Camellia sinensis, and Allium sativum as Food Additives on Metabolic Disorders, a Literature Review - Anaeigoudari, Akbar; Safari, Hamidreza; Khazdair, Mohammad Reza (Frontiers in Pharmacology, 2021)
Objective: Metabolic disorders (MD) can disturb intracellular metabolic processes. A metabolic disorder can be resulted from enzyme deficits or disturbances in function of various organs including the liver, kidneys, pancreas, cardiovascular system, and endocrine system. Some herbs were used traditionally for spices, food additives, dietary, and medicinal purposes. Medicinal plants possess biological active compounds that enhance human health. We aimed to provide evidence about therapeutic effects of some medicinal herbs on MD. Data Sources: PubMed, Scopus, and Google Scholar were explored for publications linked to MD until February 2021. The most literature reports that were published in the last 10 years were used. All types of studies such as animal studies, clinical trials, and in vitro studies were included. The keywords included “Metabolic disorders,” “Nigella sativa L.,” “Thymoquinone,” “White tea”OR “Camellia sinensis L.” “catechin,” and “Allium sativum L.” OR “garlic” were searched. Results: Based on the results of scientific studies, the considered medicinal plants and their active components in this review have been able to exert the beneficial therapeutic effects on obesity, diabetes mellitus and non-alcoholic fatty liver disease. Conclusions: These effects are obvious by inhibition of lipid peroxidation, suppression of inflammatory reactions, adjustment of lipid profile, reduction of adipogenesis and regulation of blood glucose level.